2014
DOI: 10.1128/cmr.00031-13
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Neonatal Sepsis

Abstract: SUMMARY Early-onset sepsis remains a common and serious problem for neonates, especially preterm infants. Group B streptococcus (GBS) is the most common etiologic agent, while Escherichia coli is the most common cause of mortality. Current efforts toward maternal intrapartum antimicrobial prophylaxis have significantly reduced the rates of GBS disease but have been associated with increased rates of Gram-negative infections, especially among very-low-birth-weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
649
3
51

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 808 publications
(780 citation statements)
references
References 297 publications
18
649
3
51
Order By: Relevance
“…This was agreed with Tsai et al (13) who detected that E.coli is more common in premature infant and sepsis onset on the 1 st day of life than non-E.coli, also Simonsen et al (14) ; Shah and Padbwy (15) , revealed in their study that E.coli is the organism most frequently involved in early onset sepsis. More over Liaquat et al (16) concluded that gram negative bacteria are the commonest cause of neonatal sepsis, and in their study they showed that E.coli is the most common gram negative bacteria causing neonatal sepsis.…”
Section: Discussionsupporting
confidence: 80%
“…This was agreed with Tsai et al (13) who detected that E.coli is more common in premature infant and sepsis onset on the 1 st day of life than non-E.coli, also Simonsen et al (14) ; Shah and Padbwy (15) , revealed in their study that E.coli is the organism most frequently involved in early onset sepsis. More over Liaquat et al (16) concluded that gram negative bacteria are the commonest cause of neonatal sepsis, and in their study they showed that E.coli is the most common gram negative bacteria causing neonatal sepsis.…”
Section: Discussionsupporting
confidence: 80%
“…Estados Unidos del 2005 al 2008, la tasa de letalidad fue de 10,9%, aumentando en pretérminos según (negros con 24,4% y blancos con 21,5%) en comparación con neonatos a término (negro con 1,7% y blanco con 1,6%) (7) . En un estudio chileno, la mortalidad asociada a sepsis neonatal ha permanecido baja (2,2%) (19) .…”
Section: Discussionunclassified
“…Esto resulta importante al redundar en un menor tiempo de inicio de tratamiento y, probablemente, en disminuir la elevada carga de morbimortalidad asociada a sepsis neonatal (6) . En Estados Unidos, del 2005 al 2008, la mortalidad asociada a sepsis neonatal fue de 10,9% (7) . En Perú, no se ha reportado la mortalidad asociada.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Current efforts toward maternal intrapartum antimicrobial prophylaxis have significantly reduced the rates of GBS disease but have been associated with increased rates of Gram-negative infection especially among very low birth weight infants. 4 The most common risk factors are pre maturerupture of membrane (>18 hr prior to delivery), maternal fever, maternal urinary tract infection, vaginal colonization with GBS, low levels of maternal antibody to GBS, and the presence of chorioamnionitis, 5 foul smelling liquor, multiple digital vaginal examinations, poor maternal nutrition, prematurity/Low birth weight, congenital anomalies, complicated or instrumentassisted delivery, low sapgar score (score of <6 at 5 min) and low socio economic status. 4 Sepsis in neonates may be difficult to differentiate from other conditions because the clinical signs are nonspecific.…”
Section: Introductionmentioning
confidence: 99%